Differentiation of frontotemporal dementia from dementia with Lewy bodies using FP-CIT SPECT. Issue 11 (6th August 2012) - Morgan, Shirlony; Kemp, Paul; Booij, Jan; Costa, Durval C; Padayachee, Shalandran; Lee, Lean; Barber, Christopher; Carter, Janet; Walker, Zuzana
Abstract : Introduction: There is increasing evidence that imaging with [ 123 I]FP-CIT SPECT is helpful in differentiating dementia with Lewy bodies (DLB) from Alzheimer's disease (AD) but it is not known how well the scan performs in differentiating DLB from frontotemporal dementia (FTD). Method: We compared the striatal dopamine transporter (DAT) binding in FTD (n=12), DLB (n=10) and AD (n=9) by visually rating the caudate and putamen on [ 123 I]FP-CIT SPECT scans. Results: The majority (9/10) of DLB cases had an abnormal scan and a significant reduction of uptake of DAT binding in the putamen and the caudate. A third (4/12) of the FTD cases also had an abnormal scan and a significant reduction in uptake in the putamen and the caudate. In contrast, only one out of nine AD cases had an abnormal scan. Significant differences were found when comparisons were made between the groups for visual analysis of the entire scan (p=0.001) and the four regions of interest (p=0.001 – 0.013). In contrast to the AD group (specificity of scan 89%), the specificity of [ 123 I]FP-CIT SPECT scans was reduced in the FTD group to 67%. Three quarters of the study population had at least one extrapyramidal motor sign (EPMS), with bradykinesia being the most common EPMS in both FTD (83%) and DLB (70%). Conclusions: This study highlights to clinicians that a positive (abnormal) [ 123 I]FP-CIT SPECT scan, even in a patient with an EPMS, does not exclude the diagnosis of FTD and emphasises the importance of a comprehensive clinical evaluation and a detailed cognitive assessment.